Desenvolvimento tecnológico de nanocápsulas para a liberação controlada do neuroprotetor vimpocetina - Bolson, Sabrina Negrini (2015)
The Vinpocetine is a synthetic derivative of the vincamine alkaloid, which has a significant neuroprotective effect and is used in the treatment of neurodegenerative diseases such as Alzheimer's and Parkinson's, as well as chronic cerebrovascular ischaemia and senile brain dysfunction. However, this drug has limited solubility in water and undergoes extensive first pass metabolism, resulting in low bioavailability when administered orally. In this sense, nanostructured systems have been developed aimed at improving the oral bioavailability of this substance. Therefore, this study aimed to develop of vinpocetine-loaded ethylcellulose nanocapsules using coconut oil (CO) or medium chain triglycerides (MCT) as oily cores, due to the potential of these colloidal systems for the delivering of lipophilic substances, resulting in controlled release and improvement in oral bioavailability of drugs. It was also evaluated the feasibility of converting the original suspensions in redispersible lyophilized and an in vitro preliminary cytotoxicity assay (fibroblasts) of the developed systems was conducted. According to the results, after preparation, the nanocapsule suspensions containing vinpocetine showed appropriate physico-chemical characteristics, presenting average diameters less than 200 nm, low polydispersity index (PdI), negative zeta potential and high encapsulation efficiency. The formulations were stable as the average diameter and the drug content remained above 90%, after 90 days of storage. All nanocapsule suspensions showed controlled release of vinpocetine when compared to the diffusion of free drug, and the type of oil/polymeric molecular weight influence the rate and the release mechanism of vinpocetine (phosphate buffer pH 6,8: ethanol 70:30 v/v). Furthermore, the release/dissolution of the drug from a commercial tablet was slower than (t1/2 of 91 h) from nanostructured formulations (t1/2 46-87 h). The lyophilized prepared from suspensions (containing trehalose as cryoprotectant) showed vinpocetine content between 96 and 98%, which remained unchanged after 90 days of storage. Using electron microscopy, it was observed the presence of spherical colloidal structures in dry products and the resuspension indexes in water were between 0,93 and 1,33, depending mainly on the molecular weight of the polymer. In the preliminary assay, it was observed that the nanostructures presented potential to reduce the toxicity of vinpocetine in the evaluated concentration. In view of this, the developed systems are considered promising for the controlled release of vinpocetine.